2017
DOI: 10.1111/bjd.15596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the reliability of the Cutaneous Dermatomyositis Disease Area and Severity Index and the Cutaneous Assessment Tool-Binary Method in juvenile dermatomyositis among paediatric dermatologists, rheumatologists and neurologists

Abstract: Background The Cutaneous Dermatomyositis Disease Area and Severity Index (CDASI) and Cutaneous Assessment Tool-Binary Method (CAT-BM) have been shown to be reliable and valid outcome measures to assess cutaneous disease in adult dermatomyositis (DM) and juvenile DM (JDM), respectively. Objective This study compared the CDASI and CAT-BM for use by pediatric dermatologists, pediatric rheumatologists, and pediatric neurologists in patients with JDM. Methods Five pediatric dermatologists, five pediatric rheuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Our study had several limitations, including the small sample size of 11 patients. However, despite the small sample size, the inter‐ and intrarater reliabilities for activity were still excellent, and the results are similar to those achieved in other validation studies . Another limitation is that recall bias may have been introduced during the rerater session, affecting intrarater reliability.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our study had several limitations, including the small sample size of 11 patients. However, despite the small sample size, the inter‐ and intrarater reliabilities for activity were still excellent, and the results are similar to those achieved in other validation studies . Another limitation is that recall bias may have been introduced during the rerater session, affecting intrarater reliability.…”
Section: Discussionsupporting
confidence: 79%
“…The skin PGA is a tool that estimates overall skin disease severity and has been used in multiple validation studies for skin diseases . It requires physicians to score the patient's skin‐related health on a 0–10 scale (0 = worst skin condition imaginable, 10 = perfect health) for his or her overall skin score, skin activity and skin damage.…”
Section: Methodsmentioning
confidence: 99%
“…Another prior research study similar to the current research study conducted in approach and methodology have revealed and displayed that CLASI activity scoring system had excellent inter-rater reliability in comparison to PGA, that revealed good inter-rater reliability. Interestingly it is well known that, the activity scoring is a www.opastonline.com more a more valuable measure Than damage scoring since current skin disease activity levels is measured in clinical trials [2,4,9]. Furthermore, in harmony and great similarity to the current research study it was shown that generally CLASI scoring system is more trustworthy than tool than the PGA system especially in evaluation of children diseases activity levels [11,13].…”
Section: Discussionsupporting
confidence: 59%
“…Cutaneous lupus in pediatric patients is a chief issue causing morbidity, quality of life impairment and psychosocial insults. Proper assessment permits proper and improved management protocols evaluation therefore aiding in enhancement level of care in those categories of cases among pediatric population [9,10].…”
Section: Wwwopastonlinecommentioning
confidence: 99%
“…Recent published work evaluating the Cutaneous Dermatomyositis Disease Area and Severity Index (CDASI) and the Cutaneous Assessment Tool Binary Method (CAT-BM) in JDM confirms the reliability of both tools when used by paediatric dermatologists or rheumatologists. 49 …”
Section: Discussionmentioning
confidence: 99%